And ENEM how is it? Expectations of the deaf education in COVID-19 time in and post pandemic - Gabriella Cristina de França Silva Santos; Flávia Roldan Viana (Universidade Federal do Oeste da Bahia, 2021)
The past few weeks have increasingly shown the difference in the impact of the closure of public and private educational institutions due to the public health emergency of national importance, due to the human infection with the new Coronavirus (SARS-CoV-2), cause of COVID-19. And in this scenario, the situation of deaf students in the 3rd year of high school is worsening and will take the ENEM in 2020. Therefore, the objective of this essay is to analyze the expectations of deaf students enrolled in high school at a public school in the state of RN, about ENEM at this time of COVID-19 pandemic and post-pandemic. The case study was used as a research method. The essay showed as results that it is necessary to reflect on the role of the school in inclusive education for the deaf, which is marked by ignorance and lack of linguistic policies that serve this student.